Peran Kader Posyandu dalam Upaya Pencegahan Stunting - Yasmine, Hanna Alya; Setyorini, Dyah; Yulianita, Henny (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the Posyandu cadres' role in preventing stunting in the Linggar Community Health Center area, Rancaekek District. The method used in this research is descriptive quantitative with cross-sectional. The research results illustrate that Posyandu cadres have good roles (53.2%) and poor roles (46.8%). The role of cadres as growth monitors is the highest cadre role (59.5%), and the role of cadres as managers is the lowest cadre role (57.7%) in efforts to prevent stunting. In conclusion, the majority of Posyandu cadres in the Linggar Community Health Center area play an excellent role in efforts to prevent stunting. Keywords: Posyandu Cadres, Role, Stunting